Infections in Neurosurgical Intensive Care Patients: A 3-Year Study in a Tertiary Health Care Center, North India - Chaturvedi, Deepa; Jena, Pragnya P.; Tarai, Bansidhar; Sandhu, Kavita (Journal of Neuroanaesthesiology and Critical Care, 2019)
Background In the neurosurgical patient community, infection rate depends on the severity of neurological injuries at the time of presentation, which is measured by the Glasgow coma score (GCS). In addition, associated comorbidities; exposure to invasive devices such as endotracheal tube, central venous catheters, and urinary catheters; and neuroscience-specific devices, such as ventricular/lumbar catheters, increase chances of infection. We share our experience from a dedicated neurosurgical intensive care unit (NSICU) of a super speciality tertiary care hospital in north India.Patients and Methods This is a 3-year retrospective and observational study from January 2014 to December 2016. Total 2,608 patients were admitted to NSICU during this period; 229 patients were included whose cultures were collected after 48 hours of admission and were positive. We have analyzed patient's risk factors, length of stay (LOS), outcome, organism details, and those health care–associated infections (HAI) that fulfilled the CDC (Centers for Disease Control and Prevention) criteria.Results Out of 2,608 patients admitted, 229 were culture positive after 48 hours of admission and 53 developed HAIs (53/2,608 [2.03%]). Male-to-female ratio was 2:1. One hundred three patients had a low GCS (5–8) and 126 had a high GCS (9–15). Average LOS in ICU was 6 days, and mortality was 17.4% (40/229). A total of 57 laboratory-confirmed positive cultures were identified in 53 patients. This included 35 from urine, 15 from blood, 2 from surgical wound, and 1 from respiratory tract. Among the HAI, the rate of ventilator-associated pneumonia (VAP) was 0.22, central line-associated bloodstream infection (CLABSI) 3.43, catheter-associated urinary tract infection (CAUTI) 5.93, and surgical site infection (SSI) 0.9%.Conclusion Neurosurgical patients are particularly vulnerable to infection because of the formidable nature of their illness, frequency of associated trauma, and presence of invasive devices. In our study, lower rate of HAIs was observed because we have a dedicated NSICU, strict infection control practices, an appropriate antimicrobial stewardship program, and early shifting of neurosurgical patients to an appropriately staffed high-dependency unit/ward.
Keywords: infections; neurosurgical intensive care unit; risk factors; lumbar and ventricular drain; Glasgow coma score